Bruton’s Tyrosine Kinase Supports Gut Mucosal Immunity and Commensal Microbiome Recognition in Autoimmune Arthritis - Bonami, Rachel H.; Thurman, Christina E.; Verma, Sonam; Westlake, Camille S.; Nyhoff, Lindsay E.; Barron, Bridgette B.; Reboldi, Andrea; Kendall, Peggy L. (Frontiers in Immunology, 2022)
Bruton’s tyrosine kinase (Btk) deficiency preferentially eliminates autoreactive B cells while sparing normal humoral responses, but has not been studied in mucosal immunity. Commensal microbes and intact BTK signaling have been independently shown to be essential for arthritis development in K/BxN mice. Here, we examine how BTK-mediated signaling interfaces with the gut microbiome. Btk-deficient K/BxN mice were found to have small Peyer’s Patches with reduced germinal center and IgA class-switched B cells. IgA-switched plasma cells in small intestines were reduced, especially in villi of Btk-deficient mice. CDR3 sequencing showed similar V gene diversity and somatic hypermutation frequency despite Btk deficiency but showed reduced CDR3 amino acid polarity, suggesting potential qualitative differences in the gut plasma cell repertoire. Small intestinal IgA was low and IgA coating of commensal bacteria was reduced. IgA-seq showed a shift in small intestinal microbes that are normally IgA-coated into the uncoated fraction in Btk-deficient mice. Overall, this study shows that BTK supports normal intestinal IgA development in response to commensals.